Politician Careers and SEC enforcement against financial misconduct - Mehta, Mihir N.; Zhao, Wanli (Journal of Accounting and Economics, 2020)
We document that corporate financial misconduct has significant consequences for politicians' election outcomes and, in particular, those politicians that serve on U.S. congressional committees with SEC-relevant oversight responsibilities (“SEC-relevant politicians”). These politicians display a 31% greater likelihood of losing a reelection campaign after a local firm faces SEC enforcement for financial misconduct. We also document that SEC-relevant politicians appear to influence the SEC to limit career effects due to the potential consequences from enforcement against local firms. First, the timing of enforcement action announcements around SEC-relevant politicians' elections appears opportunistic. Second, firms in the districts of SEC-relevant politicians are less likely to receive SEC enforcement actions relative to other firms and, when faced with enforcement, receive smaller penalties. Collectively, these results suggest that politicians' career concerns impede the SEC's enforcement efforts.